Marketing proactivo en tiempo de crisis para mejorar el desempeño de las mipymes del sector calzado de la ciudad de Latacunga - Analuisa Chasi, Mayra Rocío (2017)
The present research is focused on the low level of performance of the MIPYMES in the footwear sector of the Latacunga city. The goal of the project is to determine proactive marketing strategies in times of crisis for performance improvement of micro, small and medium business in the footwear area. For what a diagnosis was made based on the orientation to the customer, about cross-functional coordination and orientation to competition, in order to investigate and identify the development of both internal and external commercial activities to determine the strengths, weaknesses, opportunities and threats that directly influence the development of the business. The methodology that was used for the advance of the research was qualitative and quantitative the same as helped obtaining the necessary information, it used research techniques such as observation, interview and the survey applied to external customers of the Latacunga city. The research will contribute to MIPYMES in the footwear sector, which will allow the business owners to take decisions aimed at success and carry out marketing activities in environments exposed to the risks and economic turbulences. The impact is reflected at the economic sector that contributes to develop it, the satisfaction of the needs and expectations of consumers, seeking to obtain high levels of performance and the fidelization of them, in such a way that the companies can take the crisis as an opportunity and using those activities focused on the use of resources and efforts to improve business performance. Finally, some strategies were developed to the service, promotion, distribution and publicity of the footwear business, in order to increase the level of sales, the survival and competitiveness of the same in the market.